Observed Characteristics and Seasonality of the Diurnal Patterns of Precipitation over Metro Manila, Philippines - Olaguera, Lyndon Mark P (Archīum Ateneo, 2024)
This study investigates the diurnal pattern of precipitation over Metro Manila in terms of precipitation amount (PA), precipitation frequency (PF), and precipitation intensity (PI) using data from a dense network of automated weather stations from 2013 to 2018. The analysis was conducted for the southwest (May to September; MJJAS) and northeast (November to March; NDJFM) monsoon seasons, and for the two transition months in April and October to examine the seasonality of the diurnal patterns of precipitation. The area averaged diurnal cycle of PA over Metro Manila during MJJAS shows two peaks around early afternoon (14:00 LST; Local Standard Time), coinciding with the peak of PI, and early evening (18:00 LST), coinciding with the peak of PF. The area averaged diurnal cycle of PA during NDJFM is lower in magnitude than during the MJJAS season and shows three peaks occurring at 01:00 LST, 16:00 LST, and 20:00 LST, in which the first and third peaks nearly coincide with the peaks of PI. During April, two peaks in PA were found between 12:00 − 15:00 LST and 18:00 − 21:00 LST, while during October, PA, PF, and PI all have two peaks between 10:00 LST − 20:00 LST and 21:00 LST − 06:00 LST. Examination of the diurnal variations in surface winds and the contribution of short (1 − 3 consecutive hours), medium (3 − 6 consecutive hours), and long (> 6 consecutive hours) duration events shows that high values of PA in the two seasons and transition months coincide with high surface winds, or where there is surface wind convergence over Metro Manila. In addition, short duration events contributed more to the observed peaks of PA. The results of this study could serve as a basis for improving numerical models in representing the diurnal cycle of precipitation over Metro Manila.